ТЕОРЕТИЧНА ПІДГОТОВКА МАЙБУТНІХ УЧИТЕЛІВ ХУДОЖНІХ СПЕЦІАЛЬНОСТЕЙ НА ОСНОВІ ІНТЕГРАЦІЇ МИСТЕЦЬКИХ ЗНАНЬ (Педагогіка вищої та середньої школи, 2006)
The article deals with problem of modem approaches to setting up theoretical training (based on integration knowledge} of would ba teachers of fine arts.